Exploring New Boundaries to Mitigate Structural Vibrations of Bridges in Seismic Regions: A Smart Passive Strategy. (29th May 2016) - Maddaloni, Giuseppe; Caterino, Nicola; Nestovito, Gianluca; Occhiuzzi, Antonio
Abstract : The combined use of two emerging technologies in the field of seismic engineering is investigated. The first is a semiactive control, to reduce smartly the effects induced by earthquakes on structures. The second is the Seismic Early Warning System which allows an estimate of the Peak Ground Accelerations of an incoming earthquake. This paper proposes the exploitation of this information in the framework of a semiactive control strategy based on the use of magnetorheological (MR) dampers. The main idea consists of changing the MR dampers' behaviour by the PGA estimated by the SEWS, to obtain the optimal seismic response of the structure. The control algorithm needed to drive the variable devices, according to the PGA estimate, is the core issue of the proposed strategy. It has been found that different characteristics of earthquakes that occur at different sites play a significant role in the definition of a control algorithm. Therefore, a design procedure for "regional" control algorithms has been performed. It is based on the results of several nonlinear dynamic simulations performed using natural earthquakes and on the use of a multicriteria decision-making procedure. The effectiveness of the proposed control strategy has been verified with reference to a highway bridge and to two specific worldwide seismic regions.